Secure computer and network systems : - Ye, Nong (J. Wiley & Sons, 2008)
Secure Computer and Network Systems: Modeling, Analysis and Design is an up-to-date resource for practising engineers and researchers involved in security, reliability and quality management of computer and network systems. It is also a must-read for postgraduate students developing advanced technologies for improving computer network dependability.